ANALYSIS OF T HELPER SUBPOPULATIONS (Th1, Th2, Treg, Th17, ACTIVATED T-HELPERS) BY MEANS OF FLOW CYTOMETRY - S. V. Khaidukov; A. V. Zurochka (Медицинская иммунология)
Abstract. Over last years, huge efforts are made in order to improve analytic techniques for T lymphocyte subpopulations. Appropriate studies on T-helper cells are also subject to extensive research. These cellular compartments are substantially divided into various sub-classes. Such subpopulations, e.g., Th1, Th2, T-reg, Th17 and activated Т-helpers, were classified and characterized to sufficient degree. Recently, a lot of distinct data  about  specific  receptors  and  functional  properties  of  various  Т-helper  subpopulations  was  obtained. Applications of these results in laboratory research, without any doubt, will improve diagnostic quality when assessing functional alterations of immune system, as well as adequate therapy planning. (Med. Immunol., 2011, vol. 13, N 1, pp 7-16)